Interpersonal Needs and Relationship Satisfaction among Young Adults - Smridhi Chawla; Dr. Roopali Sharma (International Journal of Indian Psychȯlogy, 2025)
This study investigates the relationship between interpersonal needs—Perceived Burdensomeness (PB) and Thwarted Belongingness (TB)—and Relationship Satisfaction (RS) in young adults aged 18–24, based on the Interpersonal Theory of Suicide. A total of 80 participants (40 single, 40 in relationships) were selected through purposive sampling. Standardized tools—the Interpersonal Needs Questionnaire (INQ-15) and the Relationship Assessment Scale (RAS)—were used for data collection. Analysis through SPSS revealed significant negative correlations between PB, TB, and RS, indicating that higher interpersonal distress is linked to lower relationship satisfaction. While individuals in relationships reported higher RS than singles, there were no significant group differences in PB and TB, suggesting that being in a relationship does not necessarily reduce interpersonal distress. Overall, the study highlights the importance of internal emotional states in shaping relational well-being and suggests that emotional connection matters more than relationship status alone. These findings offer valuable insights for mental health professionals working with emerging adults.